Mechanical Properties of Concrete with Various Water-Cement Ratio After High Temperature Exposure - M.I Retno Susilorini; Budi Eko Afrianto; Ary Suryo Wibowo (Jurnal Teknik Sipil, 2006)
Concrete building safety of fire is better than other building materials such as wood, plastic, and steel,because it is incombustible and emitting no toxic fumes during high temperature exposure. However,the deterioration of concrete because of high temperature exposure will reduce the concrete strength.Mechanical properties such as compressive strength and modulus of elasticity are absolutely corruptedduring and after the heating process. This paper aims to investigate mechanical properties of concrete(especially compressive strength and modulus of elasticity) with various water-cement ratio afterconcrete suffered by high temperature exposure of 500oC.This research conducted experimental method and analytical method. The experimental methodproduced concrete specimens with specifications: (1) specimen’s dimension is 150 mm x 300 mmconcrete cylinder; (2) compressive strength design, f’c = 22.5 MPa; (3) water-cement ratio variation =0.4, 0.5, and 0.6. All specimens are cured in water for 28 days. Some specimens were heated for 1hour with high temperature of 500oC in huge furnace, and the others that become specimen-controlwere unheated. All specimens, heated and unheated, were evaluated by compressive test.Experimental data was analyzed to get compressive strength and modulus of elasticity values. Theanalytical method aims to calculate modulus of elasticity of concrete from some codes and to verifythe experimental results. The modulus elasticity of concrete is calculated by 3 expressions: (1) SNI03-2847-1992 (which is the same as ACI 318-99 section 8.5.1), (2) ACI 318-95 section 8.5.1, and (3)CEB-FIP Model Code 1990 Section 2.1.4.2.The experimental and analytical results found that: (1) The unheated specimens with water-cementratio of 0.4 have the greatest value of compressive strength, while the unheated specimens with watercementratio of 0.5 gets the greatest value of modulus of elasticity. The greatest value of compressivestrength of heated specimens provided by specimens with water-cement ratio of 0.5, while the heatedspecimens with water-cement ratio of 0.4 gets the greatest value of modulus of elasticity, (2) Allheated specimens lose their strength at high temperature of 500oC, (3) The analytical result shows thatmodulus of elasticity calculated by expression III has greater values compares to expression I and II,but there is only little difference value among those expressions, and (4)The variation of water-cementratio of 0.5 becomes the optimum value.